A novel method to predict the transient start-up time for natural draft dry cooling towers in dispatchable power plants. (December 2019) - Dong, Peixin; Kaiser, Antonio S.; Guan, Zhiqiang; Li, Xiaoxiao; Gurgenci, Hal; Hooman, Kamel
Highlights: Dimensional analysis determines the variables governing the start-up process of NDDCTs. The effect of tower height H, base diameter D and temperature difference Δ T on the start-up process of NDDCT is investigated. Base diameter does not affect the start-up process of NDDCTs, while the other two factors do. The prediction model of start-up time for NDDCTs is established without crosswind, t = α H 0.3 Δ T - 0.6 . Abstract: To predict the time taken for the start-up process of NDDCTs with different geometric parameters and initial conditions under windless condition, dimensional analysis is used to first determine the significant variables governing the transient start-up process. Buckingham Pi theorem is subsequently adopted to identify the relationship between the air mass flow rate through the tower and the time-taken during the start-up process of NDDCTs. Then, numerical tests are carried out to investigate the start-up process of NDDCTs with different geometric parameters including the tower height H, ( H  = 20 m, 40 m, 60 m and 80 m) and base diameter D, ( D  = 8 m, 10 m and 12 m) over a range of initial condition, i.e., when the temperature difference between the heat exchanger and the ambient air Δ T, varies from = 20 K to 40 K. The numerical results demonstrate that the base diameter will not affect the time taken during the start-up process of NDDCTs in the absence of cold air inflow, i.e., when no cold air intrudes into the tower from the top. However, the time taken for the start-up process of an NDDCT rises with the increase of the tower height, but is shortened with the increase of air-heat exchanger temperature difference. Finally, an accurate mathematical model is established based on both dimensional analysis and numerical tests to predict the start-up time leading to t = α H Δ T 2 0.3 .